IMPLEMENTASI KEGIATAN KEAGAMAAN DALAM MENGEMBANGKAN KARAKTER RELIGIUS DAN TANGGUNG JAWAB SOSIAL - Valensia, Clara; Muhammad, Suaib; Tharaba, M. Fahim (Universitas Negeri Makassar, 2022)
Research objectives Efforts to regenerate character education can be pursued by implementing religious activities in developing religious character and social responsibility. The type and approach of the research is qualitative with the type of case study research. Methods of data collection is done by using interviews, observation, and documentation. The results of this study illustrate that: 1) The forms of religious activities include: tadarus Al-Qur'an, dhuha prayer, memorizing the Qur'an, memorizing hadith used in daily life, praying dzuhur in congregation in the school mosque, studying Arabic, infaq which is done every Friday. 2) school policy in which in this case all school members participate in all forms of religious activities implemented by the school and create a religious atmosphere by setting a schedule for implementing religious activity programs. 3) The impact of the implementation of religious activities of religious character and social responsibility as follows: a) Good morals of students to teachers and older people, b) Have a high spirit of mutual help, c) Have high honesty, d) Have faith and deep devotion.